Erythrasmoid pityriasis versicolor: three case reports and review of the literature - Stefano Veraldi; Italo Francesco Aromolo; Francesca Sara Germiniasi; Gianluca Nazzaro (Dermatology Reports, 2024)
Pityriasis versicolor is characterized clinically by slightly scaly, hyper- or hypopigmented macules usually located on the chest, shoulders, back and arms. Rare cases of atypical locations of pityriasis versicolor have been described, such as groins, penis and perineum. We present three cases of pityriasis versicolor located exclusively on the submammary folds, pubis and inguinal folds (the latter in an 11-year-old girl), respectively. In consideration of both location and clinical presentation of pityriasis versicolor in these three patients, we think that the diagnosis of “erythrasmoid” pityriasis versicolor is acceptable. Differential diagnosis with erythrasma must be taken into consideration. Mycological and bacteriological examinations are therefore necessary in order to make a correct diagnosis and specific therapy.